Reconfigurable Smart Antenna for Wireless Communication Devices - Pratap Singh Sengar, Anand; Dahiya, Aman (International Journal of Engineering and Technology, 2018)
In this paper a frequency reconfigurable antenna is proposed.Â The antenna uses electrical switching by means of PIN diodes to achieve reconfigurable properties. PIN diodes are located such that to increase the total effective surface area and simultaneously the surface current. Three slots are cut from antenna to alter the surface current and improve the resonant frequency of the antenna. The location of the PIN diodes is based on optimization in the response. Diode 1 is placed to excite another patch when it will be in ON state whereas diode 2 is used to make an interconnect.Â Antenna resonates at 0.915 GHz, 1.575 GHz and 2.4GHz depending on whether it is in ON or OFF state. Applications of the antenna include GSM900 (0.8GHz-0.955 GHz), GPS (1.575 GHz), WLAN (2-2.4GHz).Â Â Â